Initial teacher education under new school development: False policy promises and their implications - Godlove Lawrent (Social Sciences and Humanities Open)
The influence of educational reforms on teachers is scarcely investigated. This study, therefore, explored the implications of the secondary education expansion policy in Tanzania for the teaching profession. A qualitative case study approach was adopted to gain a better understanding of the phenomena under exploration. Focus group discussions, one-to-one interviews, and document analysis were used for data collection. It was revealed that strategies geared towards enhancing the success of the secondary education development policy, especially those related to producing high-quality teachers to teach the newly built schools were not fully implemented. Challenges related to the admission process for, and the delivery of, pre-service programmes adversely affected the social positioning of teachers, and consequently, their identity construction was severely compromised. Reshaping the pre-service programmes in ways that enhance teachers’ sense of themselves as professionals would make teaching an appealing and promising job, and ironically the expansion policy would be effectively accomplished.